2013
DOI: 10.1002/ajhb.22383
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between diurnal changes in blood pressure and catecholamines among Filipino‐American and European‐American women

Abstract: The relationships between diurnal BP and catecholamine variations differ by ethnicity. Further research is needed to better understand the mechanisms behind the differences and to evaluate whether this vascular tonic relationship has been the focus of natural selective processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 14 publications
(19 reference statements)
1
12
0
Order By: Relevance
“…Previous studies have shown that the BPs of African-American and Asian-American women decline proportionately less from waking environments to sleep than those of European-American women (Brown et al 2003, Van Berge-Landry et al 2013, van Berge-Landry et al, 2010) and the results in the present study generally confirm these findings. However, the results of both the proportional change and mean comparisons suggest that these groups also differ from Hispanic-American women in a similar pattern to European-American women.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have shown that the BPs of African-American and Asian-American women decline proportionately less from waking environments to sleep than those of European-American women (Brown et al 2003, Van Berge-Landry et al 2013, van Berge-Landry et al, 2010) and the results in the present study generally confirm these findings. However, the results of both the proportional change and mean comparisons suggest that these groups also differ from Hispanic-American women in a similar pattern to European-American women.…”
Section: Discussionsupporting
confidence: 90%
“…The patterns and extent of circadian BP variability may also be affected by the person’s genetic and cultural background (James, 2007). There are numerous studies showing that BP declines proportionately less from waking environments to sleep among African-Americans than European Americans (Agyemanga et al 2005; van Berge-Landry et al, 2010); but, there are conflicting data regarding Asians and Asian-American comparisons with European-Americans, with some studies showing no difference with European groups (Agyemanga et al 2005) while others suggest that Asian-Americans decline proportionately less (Brown et al, 2003; van Berge Landry et al, 2013). To date, nearly all studies examining ethnic effects on circadian BP variation compare another ethnicity to a European group.…”
mentioning
confidence: 99%
“…Another limitation relates to the use of urinary catecholamines as a surrogate for sympathetic activity . Yet, measurement of urinary catecholamines has been successfully applied to delineate altered sympathetic activity in various health conditions and ethnicities . Therefore, we are confident that the differences in NDRs of urinary catecholamines observed between dippers and nondippers in the present study do reflect real differences in sympathetic activity between these two study populations.…”
Section: Study Limitationsmentioning
confidence: 84%
“…This preservative has been widely used in field studies of urinary catecholamine variation over the last two decades (e.g., Harrison et al, 1981; James et al, 1985; Jenner et al, 1987; Pollard et al, 1996; Brown and James, 2000; Glover and Poland, 2002; James et al, 2004; Brown et al, 2006; Van Berge-Landry et al, 2013). The total volume of each sample was measured to the nearest milliliter and the length of time of the collection to the nearest minute.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, while numerous studies have shown that urinary catecholamine (epinephrine and norepinephrine) and cortisol as well as ambulatory blood pressure responses vary across and within daily microenvironments in a myriad of contexts (e.g. James, 1991a,b; 2013; Light et al, 1995; Luecken et al, 1997; James et al, 1993; 1996; 2004; 2008; Brown and James, 2000; Marco et al, 2000; Steptoe et al, 2000; James and Bovbjerg, 2001; Brown et al, 2006; Dettenborn et al, 2005; Van Berge Landry et al, 2008; 2010; 2013), none have evaluated whether the responses differ by parental history of hypertension. The purpose of this study was to evaluate whether the within-individual variation in urinary catecholamine (epinephrine and norepinephrine) and cortisol excretion, and ambulatory blood pressure (BP) across three daily microenvironments (work home and sleep) differed between healthy, normotensive women with and without a reported parental history of hypertension.…”
Section: Introductionmentioning
confidence: 99%